24-h severe energy restriction impairs postprandial glycaemic control in young, lean males. Issue 10 (7th November 2018) - Clayton, David J.; Biddle, Jack; Maher, Tyler; Funnell, Mark P.; Sargeant, Jack A.; King, James A.; Hulston, Carl J.; Stensel, David J.; James, Lewis J.
Abstract: Intermittent energy restriction (IER) involves short periods of severe energy restriction interspersed with periods of adequate energy intake, and can induce weight loss. Insulin sensitivity is impaired by short-term, complete energy restriction, but the effects of IER are not well known. In randomised order, fourteen lean men (age: 25 (sd 4) years; BMI: 24 (sd 2) kg/m 2 ; body fat: 17 (4) %) consumed 24-h diets providing 100 % (10 441 (sd 812) kJ; energy balance (EB)) or 25 % (2622 (sd 204) kJ; energy restriction (ER)) of estimated energy requirements, followed by an oral glucose tolerance test (OGTT; 75 g of glucose drink) after fasting overnight. Plasma/serum glucose, insulin, NEFA, glucagon-like peptide-1 (GLP-1), glucose-dependent insulinotropic peptide (GIP) and fibroblast growth factor 21 (FGF21) were assessed before and after (0 h) each 24-h dietary intervention, and throughout the 2-h OGTT. Homoeostatic model assessment of insulin resistance (HOMA2-IR) assessed the fasted response and incremental AUC (iAUC) or total AUC (tAUC) were calculated during the OGTT. At 0 h, HOMA2-IR was 23 % lower after ER compared with EB ( P <0·05). During the OGTT, serum glucose iAUC ( P <0·001), serum insulin iAUC ( P <0·05) and plasma NEFA tAUC ( P <0·01) were greater during ER, but GLP-1 ( P =0·161), GIP ( P =0·473) and FGF21 ( P =0·497) tAUC were similar between trials. These results demonstrate that severe energy restriction acutely impairs postprandial glycaemic control in lean men, despite reducing HOMA2-IR. Chronic intervention studies are required to elucidate the long-term effects of IER on indices of insulin sensitivity, particularly in the absence of weight loss.